Investigation of experimental study of biomass performance of wood pellets, palm shells, and rice husk in vacuum pressure gasification system - Novandri Tri Setioputro; Muntar Kosim; Dede Iman Saputra (Journal of Earth Energy Engineering, 2023)
The development of biomass-based renewable energy has received extra momentum due to the petroleum/coal-based energy crisis and global warming. Vacuum suction gasification is capable of creating combustible, power-generating synthesis gas. In this vacuum suction gasification, palm shells biomass and wood pellets performed better than rice husks. The production of synthetic gas was stable. It ran for 6.5 hours straight for the ability of palm shells and wood pellets to maintain sustainable temperatures in the reactor to maintain the gasification reaction. Rice husk was not suitable for this type of gasification. It did not maintain a suitable temperature for the gasification reaction to perform well. Value of heat losses in the lining of the reactor was large, more than 2,000 watts which might be the factor that prevented the rice husk from running well. Water was sprayed onto biomass at the reactor’s input to increase its hydrogen content. Oil palm shells responded well to this treatment. It produced better syngas output sustainably. The wood pellet was not responded well to water spray. It crumbled into small pieces. Rice husk is not responded well either. Syngas produced by the reactor was burned and used to boil water. In this gasification system, palm shells and wood pellets had apparent heat values of 5.62 kW and 5.41 kW, respectively. The efficiency of palm shells and wood pellets results in performances of 29.20 percent and 29.96 percent, respectively.